2013
DOI: 10.1007/s40368-013-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Tensile bond characteristics between composite resin and resin-modified glass-ionomer restoratives used in the open-sandwich technique

Abstract: The use of bonding agent improved the CR/RMGIC bond by tensile strength and strain tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…In fact, a study proposed the use of an adhesive system between the liner and composite to improve the bonding between them. [29] Based on that, it is questioned whether the set liner-composite would rip the liner material off from the dentin. Therefore, the use of an adhesive system prior to the application of the liner could also help to improve the bonding between the material and dentin, avoiding this problem.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a study proposed the use of an adhesive system between the liner and composite to improve the bonding between them. [29] Based on that, it is questioned whether the set liner-composite would rip the liner material off from the dentin. Therefore, the use of an adhesive system prior to the application of the liner could also help to improve the bonding between the material and dentin, avoiding this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Open sandwich technique, i.e., placing a glass ionomer liner up to the cavity margin, has been advocated in the past to negate the effect of shrinkage stresses at the gingival margin . This technique is especially beneficial in cases with caries extending onto the root surface or in patients at high caries risk .…”
Section: Introductionmentioning
confidence: 99%
“…Tantbirojn and colleagues reported that glass ionomer liners, placed in an open sandwich technique, exhibited pronounced inhibition zones at the dentin margin and lowered the amount of mineral loss in the vicinity of 0.25 mm from the restoration interface under in vitro demineralization challenge. Glass ionomer has mechanical properties comparable with dentin and is widely used as dentin substitute under restorations . Development of light cured glass ionomer gave the clinician a control over its setting time and allowed its use as a dentin substitute in open sandwich restorations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations